Pengaruh Dosis Abu Sekam Padi dan Pupuk Kandang Kotoran Sapi terhadap Salinitas Tanah dan Hasil Baby Buncis - Djata Ndua, Natalia Desy (BULLET : Jurnal Multidisiplin Ilmu, 2023)
− Application of organic matter could be considered as an approach to improve productivity of saline soil. Local organic matter sources that were potentially applied including rice husk and cow manure. A glass house study aimed to investigate the effect of rice husk ash and cow manure doses on soil salinity and yield of baby bean crops had been done. The experiment was a factorial trial with two factors. The first factor was dosage of rice husk ash (A) with 4 levels, namely A0 (Without rice husk ash), A1 (20 tones rice husk ash.ha-1), A2 (40 tonnesrice husk ash.ha-1), A3 (60 tonesrice husk ash.ha-1), whilst the second factor was dosage of cow manure(S) consisted of 3 levels, namely S0 (without cow manure fertilizer), S1 (20 tonescow manure fertilizer.ha-1), S2 (40 tones cow manure fertilizer.ha-1).Variables observed were salinity (EC), Na, PNT, pH, and pod fresh weight. The results showed that although there was no interaction between rice husk ash dose and cow manure fertilizer dose, the single factor of rice husk ash dose significantly affected entire variables observed. The single factor of cow manure fertilizer, on the other hand, only affected soil salinity and PNT. Single treatmentof 300 g rice husk ash.polybag-1 reduced the soil salinity from the highest value of 4.35 mmhos.cm-1 to 0.83 mmhos.cm-1, and gave the highest baby bean pod fresh weight of 24,73 g.